Option & Option Strategies - Mehta, Mansi (2012)
The main aim of this dissertation is to project the working of Options and Option Strategies. Also to show how important it is to understand that before implementing any strategy it is essential to have a view on the market and understand the strategy and its outcome. Along with the qualitative description the quantitative description of the returns associated with the Options strategies also will be depicted. In order to show the working various aspects of Option Trading have been considered. It begins with the Introduction to Options and Option sensitivities. This is followed by a Literature review comprising of the relationship between the call and put prices as well as the relationship between the option and stock prices. Also the option pricing model, namely the Black Scholes Model has been highlighted. Later on, explanations have been given on a few Options Strategies followed by position created on the market taking historical data into consideration in order to explain the overall outcome of the Strategies described depending upon the market whether the market is Bullish, Neutral or Bearish. The market used to project this is the National Stock Exchange of India. The type of market plays a very important role in determining which strategy should be chosen in a market type. With the help of examples implied from the actual market data it becomes possible to conclude which type of strategy works well in what kind of a market. Lastly the conclusion talks about the scope of this market.